The Importance Level of Islamic Tourism Attributes: Will Religiosity Distinguish? - Afred Suci; Rita Wiyati; Inova Fitri Siregar; Satria Tri Nanda (ETIKONOMI, 2024)
Research Originality: How Islamic attribute fulfilment may influence Muslim tourists' preferences has been widely known. Yet, the way the model is examined the other way around is relatively scarce in halal tourism literature. The originality of this research lies in the model use in testing the effect of companion type and destination choice, moderated by different levels of religiosity, on Muslim tourists’ assessment of the importance of Islamic attributes in halal tourism.Research Objectives: This study aims to examine the effect of Muslim tourists’ preferences in terms of companion type and destination choice, moderated by their level of religiosity, on their assessment of the importance of Islamic attributes in halal tourism. Research Methods: Friedman and Cochran's Q non-parametric tests were conducted on 189 data collected online to examine the direct effects of companion type, destination choice, and religiosity on Muslim tourists’ assessment of the importance of Islamic attributes. Model 1 of the Hayes Process Macro with binary logistic was employed to examine the moderating effect of religiosity.Empirical Results: The results showed that companion type, religiosity, and destination choice significantly affected Indonesian Muslim travellers' assessment of the importance of Islamic attributes. However, the moderating role of religiosity was not observed.Implications: The findings have implications for Muslim travellers' decision-making literature and may offer better strategies for tourism businesses to attract and retain more Muslim tourists.JEL Classification: C14, C83, Z12, Z32How to Cite:Suci, A., Wiyati, R., Siregar, I. F., & Nanda, S. T. (2024). The Importance Level of Islamic Tourism Attributes: Will Religiosity Distinguish? Etikonomi, 23(2), 433 – 448. https://doi.org/10.15408/etk.v23i1.34369.